Khazanah Semantik Leksikal Bahasa Ibu Dalam Sastra Lisan Syair Rae Raja Lima - Mare, Fransiska Jone; Leba, Bartoldus Sora (LPPM Institut Pendidikan Nusantara Global, 2025)
Mother tongue stands as a crucial identity marker for cultural continuity within a community. However, the accelerating force of globalization has intensified language shift, placing many regional languages at risk of extinction as younger generations increasingly adopt dominant national and global languages. In response to this linguistic vulnerability, traditional oral literature plays an important role as a medium for preserving and transmitting local linguistic knowledge. This study aims to describe the lexicon contained in Sayir Rae Raja Lima and to explicate its contribution to the preservation of the mother tongue. The research employed a descriptive qualitative approach through text documentation, direct observation, and interviews with native speakers. The findings reveal that Sayir Rae Raja Lima contains a rich lexicon related to natural environments, social systems, traditional practices, kinship relations, and moral values that reflect the worldview and cultural identity of the local community. These lexical items function not only as linguistic units but also as cultural symbols that maintain collective memory and intergenerational transmission of knowledge. The analysis demonstrates that oral literature can serve as an effective strategy for conserving endangered languages by revitalizing vocabulary usage, strengthening cultural pride, and encouraging community participation in language maintenance. Thus, the documentation and analysis of traditional oral texts such as Sayir Rae Raja Lima provide significant contributions to sustaining the vitality of the mother tongue and reinforcing cultural identity in the era of globalization.